Glaciology in Aberdeen. (2nd October 2019) - Rea, Brice R.; Gemmell, Alastair M. D.; Spagnolo, Matteo
ABSTRACT: The Department of Geography has been engaged with glaciological research from its early beginnings. The paper concentrates on the period from the appointment of Chalmers Clapperton in 1962 onwards, which coincides with the time when academic staff developed focused areas of research expertise. A brief biography of each of the eleven academic members of staff who worked in the area of glaciology is presented. This is followed by an overview of the recurring research themes and locations which have been revisited within glaciology over the years. It aims to provide an overview and flavour of the Department's glaciological research.